Influence of experimental thermal shifts and overcrowding on fecundity in wild females of Acartia tonsa of the Bahía Blanca estuary - Berasategui, Anabela Anhi (2014)
The copepod Acartia tonsa plays an important role in the food web of many estuaries influenced by changes due to anthropic activities, hence it is relevant to know its reproductive plasticity under stressful conditions. We examined the influence of thermal shift (6 ± 1ºC and 18 ± 1ºC) and overcrowding stress on egg production and hatching success in wild females of A. tonsa of the Bahía Blanca Estuary. Egg production rate (EP), hatching success during seven days (E7 %) and time taken to hatch 50 % of eggs (T 50) were registered. The high individual density used in the incubations caused a decrease in EP values at both temperatures. Nevertheless, all the females responded favorably to 18°C. EP and E7 % obtained at both temperatures were significantly different the values at 18ºC, being twice as high as those obtained at 6°C. T 50 values at 18ºC indicated a shorter developmental time in eggs from spring females, whereas the opposite effect was observed in eggs from winter females. Our results indicate that the reproductive performance is affected by short exposures to thermal shift. The pattern of egg production and hatching is also modified in accordance with the maternal history.